The Child as Living Donor: Parental Consent and Child Assent - Ladd, Rosalind Ekman (Cambridge quarterly of healthcare ethics, 2004)
Despite the much-discussed court cases in the 1970s that permitted some sibling-to-sibling kidney donations from minors,1 principles that can guide parental, medical, or judicial decisionmaking are neither clearly articulated nor uncontroversial.